Socialization of Self-Watering Pots from Gallon Waste for Sustainable Waste Management: Collaboration with PKK Mungkung Village, Nganjuk Regency - Hidayat, Hana Safira; Tamtamalia, Herlin Dwi Dita; Samputri , Ghea Lintang; Mubarokah, Mubarokah (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Community service activities carried out in Mungkung Village on May 15 2024 took the form of socialization and practice of decorating self-watering pots which was attended by Mungkung Village PKK women. Group 01 KKNT MBKM led this activity to educate the public about the benefits and how to make self-watering pots from used gallons, in line with the principles of Sustainable Development (SDGs), especially SDG 12 and 15. The results of this activity show that the use of waste gallons Self -watering pots are effective in providing water automatically to plants, improving the quality of plant growth, and reducing plastic waste. The discussion also includes challenges that may be faced such as arranging drainage and monitoring potted plant nutrition. The practice of decorating self-watering pots involves creative decoration techniques, strengthens community participation in sustainable activities and inspires creativity in efforts to protect the environment. This activity not only provides practical solutions for waste management, but also raises awareness of the importance of contributing to sustainable development through simple local innovations.